Evaluasi Kebijakan Program SP3OR Jawa Barat - Sopyan Rizki Haryadi; Arif Fajar Prasetiyo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This paper starts from the activities carried out labour in several periods SP3OR West Java programs undertaken by the government of West Java. It can be seen from the population in some districts in community sports activities. This study aimed to evaluate the extent to which the results and benefits of the program in the district of West Java SP3OR to cultivate and increase the number of Public Participation in sports. This study used descriptive qualitative method, as well as with research subjects labour, SP3OR and districts of Youth and Sports Department of West Java Province. Techniques of data retrieval by means of literature study and field study consisted of observations and interviews triangulation. Triangulation is done to society (the beneficiaries), Electric SP3OR and youth and Sports Department of West Java. These results indicate SP3OR program evaluation that describes the results of the program, the work done in the program, the program's ability to solve the problem of the sport, the distribution of the program at the district level and benefits program for people in the district SP3OR.